2000
DOI: 10.1002/(sici)1522-2683(20000201)21:3<679::aid-elps679>3.3.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of gel-separated tumor marker proteins by mass spectrometry

Abstract: Two-dimensional gel electrophoresis with subsequent analysis by mass spectrometry was applied to study differences in protein expression between benign and malignant solid tumors from human beast, lung and ovary cells. Cells from freshly resected clinical material were lysed and the extracts were subjected to isoelectric focusing with immobilized pH gradients followed by second-dimensional separation on 10-13% sodium dodecyl sulfate (SDS)/polyacrylamide gels. Polypeptides were identified using matrix-assisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
4

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 0 publications
1
28
0
4
Order By: Relevance
“…The differential proteins were excised from twodimensional gel and digested with trypsin as previously described (Bergman et al 2000). Briefly, the spots were washed several times with 50% acetonitrile, which was then removed.…”
Section: In-gel Protein Digestionsupporting
confidence: 55%
“…The differential proteins were excised from twodimensional gel and digested with trypsin as previously described (Bergman et al 2000). Briefly, the spots were washed several times with 50% acetonitrile, which was then removed.…”
Section: In-gel Protein Digestionsupporting
confidence: 55%
“…Specific protein differences between different types of cancer have been identified by other groups. In a recent study of breast, ovary and lung tumors, 20 differentially expressed proteins were identified [9] and in a prior study, 16 polypeptides were found to be associated with different histopathological features of lung cancer [10,11]. In a study of 25 adenocarcinomas of the lung, 12 small cell lung cancers, and 16 squamous cell tumors, by our group (manuscript submitted) an initial analysis of protein 2-D patterns uncovered a group of 52 protein spots that differed in average integrated intensity between the three groups.…”
Section: Unique Proteomic Pattern Of Small Cell Lung Cancermentioning
confidence: 99%
“…This capability becomes especially important for mapping changes that occur during cancer progression. In the transformation process changes in protein expression may result where proteins are expressed at elevated or reduced levels [17][18][19][20][21][22][23][24][25][26]. Alternatively, important mechanisms in the cancer process often involve structural changes such as sequence variations or post-translational modifications [26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%